Mesoporous ZnCo2O4 nanoflakes grown on nickel foam as electrodes for high performance supercapacitors1. Issue 26 (14th July 2015) - Cheng, Jinbing; Lu, Yang; Qiu, Kangwen; Yan, Hailong; Hou, Xiaoyi; Xu, Jinyou; Han, Lei; Liu, Xianming; Kim, Jang-Kyo; Luo, Yongsong
<x xml:space="preserve">Abstract</x> Freestanding mesoporous ZnCo2O4 nanoflake electrodes exhibit a superior pseudocapacitive performance and long-life stability.